Polyphosphate-accumulating organisms in full-scale tropical wastewater treatment plants use diverse carbon sources - Qiu, Guanglei (2020)
Enhanced biological phosphorus removal (EBPR) is considered challenging in the tropics, based on a great number of laboratory-based studies showing that the polyphosphate-accumulating organism (PAO) Candidatus Accumulibacter does not compete well with glycogen accumulating organisms (GAOs) at temperatures above 25 °C. Yet limited information is available on the PAO community and the metabolic capabilities in full-scale EBPR systems operating at high temperature. We studied the composition of the key functional PAO communities in three full-scale wastewater treatment plants (WWTPs) with high in-situ EBPR activity in Singapore, their EBPR-associated carbon usage characteristics, and the relationship between carbon usage and community composition. Each plant had a signature community composed of diverse putative PAOs with multiple operational taxonomic units (OTUs) affiliated to Ca. Accumulibacter, Tetrasphaera spp., Dechloromonas and Ca. Obscuribacter. Despite the differences in community composition, ex-situ anaerobic phosphorus (P)-release tests with 24 organic compounds from five categories (including four sugars, three alcohols, three volatile fatty acids (VFAs), eight amino acids and six other carboxylic acids) showed that a wide range of organic compounds could potentially contribute to EBPR. VFAs induced the highest P release (12.0-18.2 mg P/g MLSS for acetate with a P release-to-carbon uptake (P:C) ratio of 0.35-0.66 mol P/mol C, 9.4-18.5 mg P/g MLSS for propionate with a P:C ratio of 0.38-0.60, and 9.5-17.3 mg P/g MLSS for n-butyrate), followed by some carboxylic acids (10.1-18.1 mg P/g MLSS for pyruvate, 4.5-11.7 mg P/g MLSS for lactate and 3.7-12.4 mg P/g MLSS for fumarate) and amino acids (3.66-7.33 mg P/g MLSS for glutamate with a P:C ratio of 0.16-0.43 mol P/mol C, and 4.01-7.37 mg P/g MLSS for aspartate with a P:C ratio of 0.17-0.48 mol P/mol C). P-release profiles (induced by different carbon sources) correlated closely with PAO community composition. High micro-diversity was observed within the Ca. Accumulibacter lineage, which represented the most abundant PAOs. The total population of Ca. Accumulibacter taxa was highly correlated with P-release induced by VFAs, highlighting the latter's importance in tropical EBPR systems. There was a strong link between the relative abundance of individual Ca. Accumulibacter OTUs and the extent of P release induced by distinct carbon sources (e.g., OTU 81 and amino acids, and OTU 246 and ethanol), suggesting niche differentiation among Ca. Accumulibacter taxa. A diverse PAO community and the ability to use numerous organic compounds are considered key factors for stable EBPR in full-scale plants at elevated temperatures.